EXECUTION OF CONVICT CONFISCATED EQUIPMENT GOODS OF HUMAN TRAFICKING - Mona Lasisca Sugiyanto; Syamsuddin Muchtar; Nur Azisa (Musamus University, 2022)
Trafficking in persons is the worst form of treatment for violating human dignity. The Trafficking in Persons Act pays attention to the suffering of victims as a result of the criminal act of trafficking in persons in the form of restitution rights in order to provide compensation that must be given by the perpetrator. Restitution is calculated by LPSK as an independent institution that objectively assesses material losses to victims and the value of restitution. This study aims to analyze the restitution of victims of the crime of trafficking in persons, and how the ideal arrangements for optimizing the payment of restitution can be made by the Public Prosecutor as the executor in the criminal act of trafficking in persons. This research is a normative legal research, using a statute approach, a case approach, and a conceptual approach. The results of the study is regulations related to restitution for the crime of trafficking in persons have regulated the mechanism for payment of restitution and also technical rules for payment related to restitution itself. However, the execution is constrained because the convict prefers to carry out a substitute sentence in the form of confinement and the public prosecutor has never received an order from the court to make a forced effort in the form of confiscation after the decision has permanent legal force. The ideal arrangement for public prosecutors to optimize the payment of restitution is by optimizing the restitution consignment mechanism which is not limited to cash but also applies to the assets of the convict to anticipate the difficulties of the confiscation mechanism after a court decision. Keywords: